The risk factors of gestational hypertension in patients with polycystic ovary syndrome: a retrospective analysis - Shu Zhou; Yiping Ji; Haimei Wang (BMC, 2021)
Abstract Background The hypertensive disorders complicating pregnancy (HDCP) is common in patients with polycystic ovary syndrome (PCOS), yet the potential influencing factors remained unclear. We aimed to assess the independent risk factors of HDCP in patients with PCOS, to provide clinical evidences for the management of PCOS. Methods Pregnant PCOS patients treated in our hospital from June 1, 2018 to November 30, 2020 were approached. The personal and clinical characteristics of patients with and without gestational hypertension were evaluated. Logistic regressions were conducted to identify the independent risk factors of HDCP, Receiver operating characteristics (ROC)curve analysis was conducted to evaluate the predicting value. Results A total of 188 PCOS patients were included, the incidence of HDCP in patients with PCOS was 27.66 %. There were significant differences in the age, BMI, family history of hypertension, the history of adverse pregnancy, history of contraceptive pills use and family history of HDCP between HDCP group and no-HDCP group (all p < 0.05), and there were no significant differences in the family history of diabetes, multiple pregnancy and long-term smoking history between HDCP group and no-HDCP group (all p > 0.05). Age ≥ 27y(OR2.048, 95 %CI1.121 ~ 3.208), BMI ≥ 24 kg/m2(OR1.463, 95 %CI1.069 ~ 2.011), family history of hypertension(OR2.129, 95 %CI1.093 ~ 3.042), the history of adverse pregnancy(OR2.435, 95 %CI1.264 ~ 4.085), history of contraceptive pills use(OR3.806, 95 %CI1.184 ~ 6.102), family history of HDCP(OR1.934, 95 %CI1.016 ~ 2.774) were the independent risk factors of HDCP in patients with PCOS (all p < 0.05). ROC curve analyses indicated that those factors had good predictive value on HDCP in PCOS patients. Conclusions The incidence of HDCP in PCOS patients is relatively high. In clinical practice, medical workers should carry out early prevention and intervention measures for these risk factors to reduce the incidence of HDCP.